2000
DOI: 10.1042/bj3490343
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression of NEU3, a novel human sialidase associated to the plasma membrane

Abstract: Several mammalian sialidases have been described so far, suggesting the existence of numerous polypeptides with different tissue distributions, subcellular localizations and substrate specificities. Among these enzymes, plasma-membrane-associated sialidase(s) have a pivotal role in modulating the ganglioside content of the lipid bilayer, suggesting their involvement in the complex mechanisms governing cell-surface biological functions. Here we describe the identification and expression of a human plasma-membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 31 publications
0
55
0
Order By: Relevance
“…The increase of GD1a could be easily associated to NEU3 down-regulation, because of its high specificity toward ganglioside substrates. [19,25,57] In addition, the glycoproteins content was greatly increased and modified, giving rise to some sialylated proteins typical of the erythroid precursors. According to this data, the total sialic acid content showed a 2.5-fold increase during differentiation (Table 1).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The increase of GD1a could be easily associated to NEU3 down-regulation, because of its high specificity toward ganglioside substrates. [19,25,57] In addition, the glycoproteins content was greatly increased and modified, giving rise to some sialylated proteins typical of the erythroid precursors. According to this data, the total sialic acid content showed a 2.5-fold increase during differentiation (Table 1).…”
Section: Discussionmentioning
confidence: 98%
“…Lysosomal sialidase (Neu1) has a catabolic role in desialylating glycoproteins and glycolipids in the lysosome [18]. Plasma membraneassociated sialidase (Neu3) is localized mainly on the cell surface [19], and its association with membrane microdomains has been demonstrated [20,21]. Neu3 acts preferentially on ganglioside substrates, and therefore modulates the sialic acid content on the cell surface [22].…”
Section: Introductionmentioning
confidence: 99%
“…Their data were based on COS-7 cells transfected with MmNeu3-HA and the cell-surface proteins were selected using biotinylated and isolated by avidin-biotin-affinity chromatography, solubilizing Neu3 from lipid bilayer by carbonate extraction or by Triton X-114 phase separation. Immunofluorescence localization experiments have been reported to show that Neu3 is localized at the plasma membrane and intracellularly in fixed, permeabilized COS-7 transfected with MmNeu3-HA [36,48] or with COS-7 cells transfected pCDNAI-NEU3 [49]. Using Western blot analyses of cell lysates from THP-1 monocytes during differentiation to macrophages, Liang et al have shown that up-regulation of Neu1 and down-regulation of Neu3, whereas Neu3 mRNA decreased by 2-3-fold as revealed by RT-PCR data [22].…”
Section: Discussionmentioning
confidence: 98%
“…To date 4 members of the neuraminidase family (neuraminidase-1 (NEU1) [19][20][21]; neuraminidase-2 (NEU2) [22,23]; neuraminidase-3 (NEU3, also known as ganglioside sialidase) [24][25][26], and neuraminidase-4 (NEU4) [27,28]) with different, although partially overlapping tissue expression, intracellular localization and substrate specificity, have been identified in mammals. NEU1 was initially localized to the lysosomes [19,21], NEU2 to the cytosol [23,30,31] and NEU3 to caveolae microdomains of plasma membranes [32] as well as the endosomal and lysosomal membranes [33].…”
Section: Mammalian Neuraminidase 1 (Neu1) and Its Catabolic Rolementioning
confidence: 99%